Psychological analysis of Devkota’s Shakuntal Mahakavya - Mishra, Uma (Academic Voices: A Multidisciplinary Journal, 2013)
Article in Nepali. Academic Voices, Vol. 2, No. 1, 2012, Pages 74-77 DOI: http://dx.doi.org/10.3126/av.v2i1.8293